FORTIFICATION LANDSCAPES: THE NATURE AND CLASSIFICATION - Denysyk, H. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The problem of the use and understanding of the concept "fortification landscapes", their nature and classification capabilities have been considered. Great diversity of fortification landscapes made it possible to classify them according to time of formation, duration of existence, commercial use, belonging to the types of areas. From the viewpoint of landscapes, the most appropriate classification of fortification landscapes is belonging to corresponding types of areas. General classification of fortification landscapes is represented by the scheme, which singles out the class, subclasses, zonal types, fortificaton areas, parcels and natural boundaries. The possibilities of fortification landscapes rational use have been partially considered.
Keywords: landscape, fortification landscape, nature, classification, types, mounds, fortifications